PENGARUH PENGETAHUAN PAJAK, SANKSI PAJAK, PELAYANAN PAJAK, DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DENGAN SOSIALISASI PERPAJAKAN SEBAGAI VARIABEL MODERASI - Nurul Dwi Afisah; Banu Witono (ITB AAS Indonesia Surakarta, 2023)
This study aims to determine and analyze the effect of tax knowledge, tax sanctions, tax services, and taxpayer awareness on motor vehicle taxpayer compliance, with tax socialization as a moderating variable. Sampling in this study used the accidental sampling technique by sending questionnaires to motor vehicle taxpayers and obtaining a sample of 100 respondents. Data analysis in this study used multiple linear regression analysis and the Moderated Regression Analysis (MRA) test. The data analysis used SPSS version 25. The results showed that tax knowledge, tax sanctions, and taxpayer awareness positively and significantly affected motor vehicle taxpayer compliance. Tax services do not affect motor vehicle taxpayer compliance. Tax socialization is not able to moderate the influence of tax knowledge, tax services, and the awareness of taxpayers on motor vehicle taxpayer compliance. Tax socialization weakens the effect of tax sanctions on motor vehicle taxpayer compliance. Keywords : Taxpayer compliance, tax knowledge, tax sanctions, tax services, taxpayer awareness, and tax socialization.